THE EFFECT OF JOB INSECURITY AND SOCIAL SUPPORT TOWARD PSYCHOLOGICAL WELL-BEING AMONG OUTSOURCED EMPLOYEES AT COMPANY X of MEDAN - Jihan Sulaiman; Sjahril Effendy; Rahmi Lubis (SEAN Institute, 2023)
The study will look at how job insecurity and social support affect the psychological well-being of outsourcing employees at company X Medan. This research used a quantitative method. This study included 109 outsourcing employees from the Company X of Medan. The measurement was conducted using the job insecurity, social support, and psychological well-being scales. Data on this research was analyzed using multiple regression tests. According to the statistics, F value 12.077 > F table 3.08 and p = 0.000 < 0,050, job insecurity and social support were affected by psychological well-being among outsourcing employees at Company X of Medan. Other findings include experienced job insecurity among outsourcing employees at Company X of Medan, perceived social support among outsourcing employees at Company X of Medan, and psychological well-being among outsourcing employees at Company X of Medan. Therefore, it is recommended that further research be carried out with qualitative methods or a mixed design and consider other variables.